Lukács' antinomic 'standpoint of the proletariat': From philosophical to socio-historical determination. (April 2020) - Jaffe, Aaron
In History and Class Consciousness ' central essay 'Reification and the Consciousness of the Proletariat', Lukács resolved the antinomies of bourgeois philosophy in the revolutionary 'standpoint of the proletariat'. Lukács' strategy in deriving this proletarian standpoint, however, transposed the logical necessity appropriate to philosophical determinations into possibilities for revolutionary praxis imbedded in socio-historical contexts. Further, since the standpoint is determined as the necessary solution to bourgeois antinomies, it must be conceived singularly, rather than through its manifest diversity. As the key to mediating the social totality beyond antinomies, the 'standpoint of the proletariat' is therefore merely reflectively posited and one-sidedly determined. While many have developed logical, social-analytic, and political problems associated with determining the proletariat by way of its imputed or party-determined rather than empirical consciousness, few point to the very concept 'standpoint of the proletariat' as the source for these problems due to the fact that it is an abstractly derived solution to a philosophically posed problem. Socio-historical determination working with the modality of possibility can resolve Lukács' antinomic determination of the standpoint of the proletariat.